NROER: The Indian OER Initiative - Sharma, Rajaram S. (JOURNAL OF INDIAN EDUCATION, 2014)
Modern day Information and Communication Technologies hold the promise of equitable access to information and resources. Combined with the concept of the creative commons, the goal of universal access to quality education has entered the realms of a common human’s aspiration. State education systems have striven against systemic, economic, geographic and socio-cultural barriers to ensure convenient access to resources of a comparable quality to all. It is in this context that the National Repository of Open Education Resources (NROER), an initiative of the National Council of Educational Research and Training and the Government of India, should be studied.